(untitled) (Confluenţe Bibliologice, 2015)
The article includes a review of the book „The Golden Book of Family Sutu” that can be considered truly a historical encyclopedia and discusses the issue not only in terms of genealogy, but refer to various ﬁelds such as geography, architecture, religion, heraldry, sigillography and medals. Its author, Radu Negrescu-Sutu, writer, journalist, translator and editor, has published several books, including: Ten memories, Essays, Light’s Gate, Concert Haendel’s Concert and Theological dialogue. The author claims that the book „is simply a genealogical study of SUȚU family without comment of this family role their played within the Ottoman Empire, in Moldova, Romanian Land and Greece. This mission thankless and diﬃcult, rests with the historians, the only ones who can prove objectively in such a case ... We wrote this book in debt to the memory of this family and I gathered the attention of future generations, a greater number of portraits, to facilitate the identiﬁcation of their ancestors. At ﬁrst sight „The Golden Book of Sutu family” impresses by its size, with 835 pages, 2 000 illustrations and a family tree with 400 people who are intelligent placed on a length of 2.20 m. Each descendant of the family is a number which can be easily identiﬁed in the card.